Evaluation of the Obulamu? integrated health communication campaign in Uganda: results from a repeated cross-sectional household survey. (3rd April 2021) - Burke, Holly M.; Okumu, Eunice; Zikusooka, Amos; Batamwita, Richard; Nalukwago, Judith; Field, Samuel; Bernholc, Alissa; Martinez, Andres; Bufumbo, Leonard; Kimbowa, Musa; Coutinho, Sheila M.; Mack, Natasha; et al.
ABSTRACT: Introduction: Uganda's Obulamu? campaign delivered messages relevant to life stage to address evolving health needs of audiences at times they were likely to change behaviors. We estimated Obulamu?'s effects on HIV/AIDS, family planning, maternal and child health, tuberculosis, malaria, and nutrition behavioral outcomes. Methods: We conducted repeated cross-sectional household surveys with women, men, and children's caregivers in 2015 and 2017 in 16 districts using multi-stage probability sampling weighted by population. Eleven pre-specified outcomes were evaluated in multivariable weighted regression models. Results: Survey 1 included 2, 377 households with 4, 012 individuals and survey 2 included 2, 398 households with 3, 563 individuals. After controlling for time and potentially confounding factors, we observed notable increases among people exposed to topic-specific messages in condom use with at least one non-marital, non-cohabiting partner in the last six months; recent male circumcision; seeking tuberculosis screening/testing for self; seeking tuberculosis screening/testing for child; delivery of baby in a facility; and caregiver seeking advice or treatment for child under five years with fever. Exposure did not appear to influence knowledge of antiretroviral therapy, delay sexual debut, breastfeeding infants and all of the household's pregnant women/children less than five years sleeping under a net the night before the survey. Conclusion: Exposure to topic-specific messages was associated with improvements in six of the eleven outcomes. Across the health priority areas, we observed improvements in select HIV/AIDS, tuberculosis, and maternal and child health outcomes. We did not observe effects of exposure on select outcomes in the areas of family planning, malaria, or nutrition.